Formation mechanism of micro/nanoscale structures on picosecond laser pulse processed copper - Mark Anderson; Graham Kaufman; Aaron Ediger; Dennis Alexander; Craig Zuhlke; Jeffrey E. Shield (Materials Today Advances, 2023)
Modification of surfaces with ultrashort pulse laser surface processing techniques has shown to enhance surface properties for numerous applications. To more effectively tailor material properties, there needs to be a better understanding of the self-organization processes that lead to the quasi-periodic micro- and nano-scale surface features. In this paper, a multi-cross-section technique was used to gain understanding of how the surface features form during processing of copper with picosecond pulses. Incremental cross-sections were performed starting at the leading edge of the final laser pass. Each subsequent cross-section moved farther away from the leading edge and towards the final microstructure seen within the center of the processed region. Utilizing the cross-sectional and laser confocal data combined with the 2D projection of the Gaussian beam profile, a progression of formation mechanisms that includes a balance of ablation, redeposition, shielding, and sintering is explained. This formation mechanism progressed with initial ablation of copper that redeposits onto the surface. The redeposited copper then acts as a protection against the high fluence portion of the laser beam allowing for the mounds to grow. The redeposited copper particles are then sintered by the tail-end of the Gaussian profile into a porous layer.